Radioactivity concentrations and dose assessment for soil samples from Kestanbol granite area, Turkey - Merdanoğlu, B.; Altinsoy, N. (Oxford University Press (OUP), 2006)
The concentrations and distribution of natural and anthropogenic radionuclides in soils from around the Kestanbol (Canakkale), Turkey were investigated with an aim of evaluating the environmental radioactivity and radiological health hazard. Concentrations of radionuclides in the samples were determined by gamma ray spectrometer using HPGe detector. In the soils in general, the concentration of (232)Th was found to be higher than that of the (238)U and the activities of (232)Th and (238)U in this area are higher than the world average. (137)Cs was observed in all the samples, ranging from 0.37 +/- 0.22 to 36.03 +/- 0.54 Bq kg(-1). The mean radium equivalent activity, external hazard index and terrestrial absorbed dose rate for the area under study are 498 Bq kg(-1), 1.4 and 219 nGy h(-1), respectively. The annual effective dose to the public was found to be 269 muSv. The present data were compared with data obtained from different countries.
Keywords: Radioisotopes; Turkey; Radiation Dosage; Silicon Dioxide; Radiation Protection; Radiation Monitoring; Background Radiation; Body Burden; Humans; Soil Pollutants, Radioactive; Relative Biological Effectiveness